Effect of Diethanolamine (DEA) Solvent Flow Rate on the CO2 Absorption-Desorption Process Using a Hollow Fiber Membrane Contactor - Pamungkas, Raditya; Nurkhamidah, Siti; Taufany, Fadlilatul; Altway, Ali; Susianto, Susianto; Rahmawati, Yeni (Eksergi, 2025)
One of the primary objectives in decarbonization is the separation of CO₂ from industrial gas mixtures, particularly in application such as biogas purification and flue gas treatment. A dual-layer crossflow membrane module was utilized under both circulation and batch operating modes with a 30% DEA solution. This study investigates the influence of solvent flow velocity on CO₂ separation performance using a hollow fiber membrane contactor with a 30% DEA solvent. the process was evaluated under two operating modes: batch and solvent circulation. Key variables measured include the solvent flow rate (40–160 mL/min), operating temperature (30–50°C), and sweep gas flow rate (100–300 mL/min). The results indicate that under continuous operation with a solvent flow rate of 160 mL/min, a temperature of 30°C, and a sweep gas flow rate of 100 mL/min, 50.42% of the CO₂ was successfully removed. In contrast, the batch system, under identical conditions achieved only a 27.8% removal rate. The superior performance in circulation mode is attributed to the continuous renewal of the solvent, which sustains a stable concentration gradient and minimizes mass transfer resistance. These findings underscore the potential of membrane-based systems with optimized solvent circulation for efficient and stable CO₂ capture in industrial applications.